E-learning Technologies in Teaching of the Discipline "Life Safety" - N. S. Malchenko (Цифровая трансформация)
At present, a teacher has access to a wide range of tools for training with use of e-learning technologies: distance learning systems, a variety of synchronous and asynchronous means of interaction, electronic library systems and others. However, the existence of the teacher access to a variety of IT-services does not mean unconditional positive results towards the realization of the goals and objectives of education. In the article it is described pedagogically grounded approach to the teaching of a particular discipline (on the example of еру discipline "Life Safety") in the terms of use of e-learning technologies.